Respostas
respondido por:
3
4 2
x - 16x
y = -------------------
x² + 10x + 24
x²(x² - 16)
y = ------------------
(x + 6)(x + 4)
x²(x + 4)(x - 4)
y = --------------------
(x + 6)(x + 4)
x²(x - 4) x³ - 4x²
y = -------------- OU y = -----------
x + 6 x + 6
x - 16x
y = -------------------
x² + 10x + 24
x²(x² - 16)
y = ------------------
(x + 6)(x + 4)
x²(x + 4)(x - 4)
y = --------------------
(x + 6)(x + 4)
x²(x - 4) x³ - 4x²
y = -------------- OU y = -----------
x + 6 x + 6
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás